The effect of avocado butter to stability of avocado emollient cream - Teti Indrawati; Yuanita Sari (Indonesian Journal of Pharmacy, 2011)
The characteristic of emollient cream that contained of avocado butter as anti-aging  is  influenced  by  amount  of  avocado  butter  used.  The  research  has  a purpose to exploit and develop usage of avocado butter in the field of cosmetic. The  research  has  done  by  making  A/M  cream  used  1-11% avocado  butter  with melting  and  mixing  method  at  temperature  of  70-75  °C.  Stability  of  product creams  were  be  evaluated,  and  tested  with  accelerated  test  using  elevated temperature.  The  result  showed  that  concentration  of  avocado  butter  between 1-11%  can  be  made  become  W/O  emollient  cream.  The  cream  stability  was progressively influenced by amount of avocadobutter, the increasing of avocado butter  would  make  progressively  good  stability,  the stability  go  down  at  7% concentration.  The  best  stability  creams  has  shown  by  cream  that  contain  5% avocado butter,Key words: avocado butter, A/M cream type, emollient cream, stability of cream